Mapping of the Glucose Metabolism Heterogeneity in Atherosclerosis: Correlation With 2-Deoxyglucose Uptake - Joseph Haddad MD; Selim Demirdelen MD; Clayton E. Barnes BS; Steven A. Leers MD; Sina Tavakoli MD, PhD (Molecular Imaging)
Objective 2-Deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) is widely used for noninvasive imaging of atherosclerosis. However, knowledge about metabolic processes underlying [ 18 F]FDG uptake is mostly derived from in vitro cell culture studies, which cannot recapitulate the complexities of the plaque microenvironment. Here, we sought to address this gap by in situ mapping of the activity of selected major dehydrogenases involved in glucose metabolism in atherosclerotic plaques. Methods In situ activity of lactate dehydrogenase (LDH), glucose-6-phosphate dehydrogenase (G6PD), succinate dehydrogenase (SDH), and isocitrate dehydrogenase (IDH) was assessed in plaques from murine aortic root and brachiocephalic arteries and human carotid arteries. High-resolution 2-deoxy-D-[1,2- 3 H]glucose ([ 3 H]2-deoxyglucose) autoradiography of murine brachiocephalic plaques was performed. Results LDH activity was heterogeneous throughout the plaques with the highest activity in medial smooth muscle cells (SMCs). G6PD activity was mostly confined to the medial layer and to a lesser extent to SMCs along the fibrous cap. SDH and IDH activities were minimal in plaques. Plaque regions with increased [ 3 H]2-deoxyglucose uptake were associated with a modestly higher LDH, but not G6PD, activity. Conclusions Our study reveals a novel aspect of the metabolic heterogeneity of the atherosclerotic plaques, enhancing our understanding of the complex immunometabolic biology that underlies [ 18 F]FDG uptake in atherosclerosis.